2017
DOI: 10.1002/ccr3.836
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in a bleeding disorder: case of thromboembolism in factor VII deficiency

Abstract: Key Clinical MessageCongenital factor VII deficiency (FVIID) is a rare disorder with a wide range of bleeding manifestations. The disorder does not protect patients against occurrence of thrombosis, and deep vein thrombosis can occur in the setting of surgery and recombinant factor VIIa replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
(10 reference statements)
0
10
0
4
Order By: Relevance
“…It has also been demonstrated that the majority of patients with FVII deficiency and thrombosis have concomitant triggering events such as immobilization, replacement therapy especially that with aFVII concentrates, oral contraceptives, surgical procedures, and pregnancy. 12,25,26 (3) FIX Defects …”
Section: Classificationmentioning
confidence: 99%
“…It has also been demonstrated that the majority of patients with FVII deficiency and thrombosis have concomitant triggering events such as immobilization, replacement therapy especially that with aFVII concentrates, oral contraceptives, surgical procedures, and pregnancy. 12,25,26 (3) FIX Defects …”
Section: Classificationmentioning
confidence: 99%
“…При проведении гемостатической терапии послеоперационные тромбозы и тромбоэмболии не являются редкостью у пациентов с гемофилией А [10], а страдающие болезнью Виллебранда при заместительной гемостатической терапии склонны скорее к тромботическим осложнениям, чем к кровотечениям [11]. Данных о частоте тромботических осложнений в период беременности у женщин с гипопроконвертинемией в литературе нет, тем не менее в целом в популяции тромбозы при гипопроконвертинемии встречаются у 3-4% больных, в том числе при тяжелой форме заболевания [12,13]. Это накладывает определенные ограничения на интенсивность проводимой гемостатической терапии.…”
Section: междисциплинарные проблемыunclassified
“…В литературе нет единого мнения о кратности введения rFVIIa. В ряде работ [5,12] рекомендуется: либо повторно вводить препарат в течение 2-3 суток, либо ограничиться однократным введением при отсутствии геморрагических проявлений. Последняя тактика и была избрана в анализируемых случаях.…”
Section: междисциплинарные проблемыunclassified
“…Bazı hastalar da asemptomatik kalabilir. Çok nadir durumlarda arteriyel ya da venöz tromboz görülebilir (1)(2)(3). Bu makalede pulmoner tromboemboli (PTE) tanısı koyduğumuz bir konjenital FVII eksikliği hastamızı literatür eşliğinde sunuyoruz.…”
unclassified
“…(5) tarafından 1951 yılında tanım-lanan FVII eksikliği kalıtsal ya da sekonder olarak görülebilir. Kalıtsal eksikliği toplumda 1/500.000 oranında görülür ve otozomal resesif olarak geçer(1,2). FVII eksikliği için 250'den fazla mutasyon tanımlanmıştır(6).…”
unclassified